Autonomy of long-stay psychiatric inpatients Autonomia de pacientes em internação prolongada em hospital psiquiátrico - Luciane Carniel Wagner; Marcelo Pio de Almeida Fleck; Mário Wagner; Míriam Thaís Guterres Dias (Universidade de São Paulo, 2006)
OBJECTIVE: To assess personal autonomy of long-stay psychiatric inpatients, to identify those patients who could be discharged and to evaluate the impact of sociodemographic variables, social functioning, and physical disabilities on their autonomy was also assessed. METHODS: A total of 584 long-stay individuals of a psychiatric hospital (96% of the hospital population) in Southern Brazil was assessed between July and August 2002. The following instruments, adapted to the Brazilian reality, were used: independent living skills survey, social behavioral schedule, and questionnaire for assessing physical disability. RESULTS: Patients showed severe impairment of their personal autonomy, especially concerning money management, work-related skills and leisure, food preparation, and use of transportation. Autonomy deterioration was associated with length of stay (OR=1.02), greater physical disability (OR=1.54; p=0.01), and male gender (OR=3.11; p<0.001). The risk estimate of autonomy deterioration was 23 times greater among those individuals with severe impairment of social functioning (95% CI: 10.67-49.24). CONCLUSIONS: In-patients studied showed serious impairment of autonomy. While planning these patients' discharge their deficits should be taken into consideration. Assessment of patients' ability to function and to be autonomous helps in identifying their needs for care and to evaluate their actual possibilities of social reinsertion. OBJETIVO: Avaliar a autonomia de uma população de pacientes com internação prolongada em um hospital psiquiátrico, identificar indivíduos com possibilidades de desinternação e avaliar o impacto de variáveis sociodemográficas, do funcionamento social e de incapacitações físicas sobre a autonomia. MÉTODOS: Foi avaliado o total de 584 indivíduos de um hospital psiquiátrico de Porto Alegre, RS, com internação prolongada (96% dois pacientes), entre julho e agosto de 2002. Foram utilizados os instrumentos, adaptados para a realidade brasileira: independent living skills survey (inventário de habilidades de vida independente), social behavioral schedule (escala de avaliação do comportamento social) e questionário de avaliação do grau de invalidez física. RESULTADOS: Os pacientes apresentaram grande comprometimento de sua autonomia, principalmente com relação à administração de dinheiro, ocupação, lazer, preparo de alimentos e transporte. A deterioração da autonomia esteve associada com o tempo de internação (OR=1,02), com severa incapacitação física (OR=1,54; p=0,01) e com o sexo masculino (OR=3,11; p<0,001). A estimativa do risco de ter um comprometimento moderado a grave da autonomia foi 23 vezes mais alta entre os indivíduos com severo prejuízo no funcionamento social (IC 95%: 10,67-49,24). CONCLUSÕES: A população avaliada apresentou sua autonomia seriamente deteriorada. Concluiu-se que no planejamento da desinternação prolongada desse tipo de paciente deve-se levar em conta seus déficits funcionais. A avaliação do funcionamento social e autonomia auxilia na identificação das necessidades e na determinação da viabilidade do processo de desinternação e reinserção social desses indivíduos.